The current status of scholarly journal publishing in Brunei Darussalam: A revisit - Hashim, Roosfa (2017)
Some new higher education institutions and research centers have emerged in Brunei Darussalam recently. In line with this development, there are also several new scientific and scholarly journals published by new higher education institutions. This paper will see new trends being developed in Brunei Darussalam today especially in the development of scholarly publishing. The focus of this paper is on the emerging journals in Brunei Darussalam. What are the fields of knowledge that offers space for new knowledge in Brunei Darussalam? The study was conducted by examining the contents of new journals in Brunei Darussalam. This study concludes that the development of knowledge is rapidly expanding in Brunei.